CNS-Spleen Axis – a Close Interplay in Mediating Inflammatory Responses in Burn Patients and a Key to Novel Burn Therapeutics - Khan, Noorisah; Kaur, Supreet; Knuth, Carly M.; Jeschke, Marc G. (Frontiers in Immunology, 2021)
Severe burn-induced inflammation and subsequent hypermetabolic response can lead to profound infection and sepsis, resulting in multiple organ failure and high mortality risk in patients. This represents an extremely challenging issue for clinicians as sepsis is the leading cause of mortality in burn patients. Since hyperinflammation and immune dysfunction are a result of an immune imbalance, restoring these conditions seem to have promising benefits for burn patients. A key network that modulates the immune balance is the central nervous system (CNS)-spleen axis, which coordinates multiple signaling pathways, including sympathetic and parasympathetic pathways. Modulating inflammation is a key strategy that researchers use to understand neuroimmunomodulation in other hyperinflammatory disease models and modulating the CNS-spleen axis has led to improved clinical outcomes in patients. As the immune balance is paramount for recovery in burn-induced sepsis and patients with hyperinflammatory conditions, it appears that severe burn injuries substantially alter this CNS-spleen axis. Therefore, it is essential to address and discuss the potential therapeutic techniques that target the CNS-spleen axis that aim to restore homeostasis in burn patients. To understand this in detail, we have conducted a systematic review to explore the role of the CNS-spleen axis and its impact on immunomodulation concerning the burn-induced hypermetabolic response and associated sepsis complications. Furthermore, this thorough review explores the role of the spleen, CNS-spleen axis in the ebb and flow phases following a severe burn, how this axis induces metabolic factors and immune dysfunction, and therapeutic techniques and chemical interventions that restore the immune balance via neuroimmunomodulation.